Notes on the African root and tuber scale, Stictococcus vayssierei Richard, a recent reported cassava pest in the BasCongo Province of the Democratic Republic of Congo - Tata-Hangy, K.W.; Lema, K.; Ndambi, N.; Lutete, D.; Hanna, R.; Toko, M.; Nkakwa, A. (2006)
The African root and tuber scale insect (ARTS)(Stictococcus vayssierei. Richard) has increasingly become a major pest of cassava in the forest areas of the Bas-Fleuve District in the most western province of the Democratic Republic of Congo where it was known since long ago without any noticeable damage on the crop. Surveys conducted in the District indicated that the pest is confined to forest zones. The level of infestations on cassava was shown to be highly influenced by the type of predominant forest vegetations where the cassava fields were established. Scale infestations were high in highly degraded secondary forests where cassava is continuously planted and low in well reconstituted forests, where fields are planted after long fallows. Wild alternative host plants were inventoried in different types of fallows and were identified. These plants are thought to serve as reservoir for S. vayssierei infesting cassava fields planted after long fallows. Furthermore, the impact of S. vayssierei attacks on cassava production was experimentally quantified and revealed a negative effect on the bulking of the storage roots and hence cassava yield. An average root yield reduction of45'/" and 60% was obtained on the tolerant and susceptible variety, respectively. This reduction in root yield could not be attributed to any other cassava constraints as at the time the experiment was conducted, the only differences among plots and between varieties were the experimentally manipulated scale infestation levels. This paper reports on the geographical distribution of S. vayssierei in the province of Bas-Congo, the host plants association, the type of damage on cassava and its effects on cassava yield. The pest has been repoded in other provinces with similar forest agro-ecologies in the country.